Students' Screen Time Towards Physical Education As an Emotion Regulation - Winda Lailani Dwi Larassati; Adi S (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the relationship between duration (screen time) and the level of self-regulation in adolescents at the high school level. The increase in penetration of digital technology is often not proportional to students' self-control abilities, so empirical evidence is needed regarding the relationship between the two. This study uses a descriptive quantitative approach with a non-parametric correlation method. The research sample consisted of 128 students who were selected using purposive sampling techniques. Data is collected through questionnaire instruments distributed online through Google Form. Data analysis was carried out using  the Spearman rho correlation test. The results showed a significant positive relationship (Very Positive) between screen time and self-regulation with a correlation coefficient of 0.992 and a significance value (Sig. 2-tailed) < 0.001. These findings show that the pattern of screen duration use is closely related to students' self-control mechanisms in the field. The conclusion of this study emphasizes the importance of strengthening self-regulation as a moderation strategy in regulating the duration of device use to support students' mental health and productivity in the digital era.